Developing a Scale: Perceptions of High School Students About the Relationship Between Chemistry and Daily Life - Altundağ, Canan Koçak; Mustafaoğlu, Fatma Merve; Yücel, Ayşem Seda (SCAD Independent, 2022)
This study aimed to develop an instrument to measure the perception of high school students regarding the relationship between chemistry and daily life and to determine the validity and reliability levels of the developed measurement tool. The data were collected from 7308 high school students from 59 provinces in Turkey. After the exploratory factor analysis was carried out to get an idea about the structure of the Perception Scale for Chemistry and Daily Life Relationship, the structure obtained was checked by confirmatory factor analysis. Originally consisting of 35 items, the load factor of the scale was decreased to 26 items following the removal of 9 items which were understood to be at a low level in item-total correlation and reliability. The Perception Scale for Chemistry and Daily Life Relationship consisted of 26 items and four factors: Awareness, Development, Interest, and Consciousness. These findings concluded that the scale obtained was valid and reliable in determining student perceptions about the relationship between chemistry and daily life. Teacher educators and chemistry teachers can use the instrument to determine high school students' perceptions of the relationship between chemistry and daily life. In this way, it may contribute to training students with potential for chemistry-related professions by implementing appropriate ways.